РАЗРАБОТКА ИММУНОФЕРМЕНТНОЙ ТЕСТ-СИСТЕМЫ ДЛЯ КОМПЛЕКСНОЙ ДИАГНОСТИКИ НАИБОЛЕЕ ПАТОГЕННЫХ ВИРУСОВ КАРТОФЕЛЯ (Experimental biology, 2015)
On the basis of the received immune globulin and conjugations an integrated diagnostic test-system was created which is able to detect PVX, PVY, PVS, PVМ, PLRV, PVA viruses of potato at the same time. Optimal characteristics of IFA arrangement were developed and chosen. Optimal characteristics of antigens potato viruses PVМ, PVS, PVY dissolving in sampling conjugation buffer in correlation 1:40 were established. Optimal incubation of virus antigens during the experiment was at the temperature +370С for 2 hours in “sandwich” IFA version.
Keywords: immune globulin; conjugation; “sandwich”